(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study article is to explore the usefulness of therapeutic hypnotherapy as a treatment for Generalized Anxiety Disorder (GAD) with regard to its long-term effectiveness. Using a randomized controlled trial methodology, the research investigates the effects of clinical hypnotherapy in comparison to the outcomes of a control group that was provided with conventional treatment. In order to examine the long-term benefits of hypnotherapy on generalized anxiety disorder (GAD) symptoms, a number of different measures of anxiety intensity, quality of life, and functional impairment are performed at the beginning of the study, after treatment, and at follow-up intervals. The results show that hypnotherapy may play a role in the comprehensive care of generalized anxiety disorder (GAD), which is an important discovery.